As x ranges across all real values, the minimum value of
( x − 1 6 ) ( x − 1 4 ) ( x + 1 4 ) ( x + 1 6 )
can be expressed as − A . What is the value of A ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Correction on line 6: It should read: 4 x 3 − 9 0 4 x = 0
Nice From (x^2 - 256)(x^2 - 196) use product rule. So it actually simplifies to 2x(x^2 - 256) + 2x(x^2 - 196)=0 So either x=0 or x^2=256+196 Sorry I had no where to post a solution
Oops, I kept wondering how root(226) was wrong. Turns out they asked for the minimum value!
microsoft mathematics ftw !!!!!!!!
one can also use am gm inequality
very good buddy!!...seems like i've to work on my math..
the answer is 899
Note that
( x − 1 6 ) ( x − 1 4 ) ( x + 1 4 ) ( x + 1 6 ) = ( x 2 − 2 5 6 ) ⋅ ( x 2 − 1 9 6 ) .
Let this function be f ( x ) . Then:
f ′ ( x ) = ( x 2 − 2 5 6 ) ⋅ ( 2 x ) + ( x 2 − 1 9 6 ) ⋅ ( 2 x ) = 2 x ⋅ ( 2 x 2 − 4 5 2 ) .
Note that f ′ ( x ) = 0 when x = 0 or x = ± 2 2 6 . At x = 0 , it is not an absolute minimum. At x = ± 2 2 6 , the function reaches the minimum of − 9 0 0 , so A = 9 0 0 .
First notice that ( x − 1 6 ) ( x + 1 6 ) ( x − 1 4 ) ( x + 1 4 ) = ( x 2 − 1 6 2 ) ( x 2 − 1 4 2 ) = ( t − 1 6 2 ) ( t − 1 4 2 ) , t ≥ 0 We then have a parabola (restricted to lie in the positive region of the t -axis. The minimum is reached in the vertex (which lies at t = ( 1 6 2 + 1 4 2 ) / 2 ≥ 0 . We find min = 4 − Δ = 4 ( 1 6 2 + 1 4 2 ) 2 − 4 ⋅ 1 6 2 ⋅ 1 4 2 = 4 ( 1 6 2 − 1 4 2 ) 2 = 4 ( 3 0 ⋅ 2 ) 2 = 9 0 0 .
Yay a solution that doesn't require calculus :P good job
There are different ways of approaching this problem. This is my way of approaching this problem:
It is obvious that
( x − 1 6 ) ( x − 1 4 ) ( x + 1 4 ) ( x + 1 6 )
= ( x − 1 6 ) ( x + 1 6 ) ( x − 1 4 ) ( x + 1 4 )
Using the algebraic identity a 2 − b 2 = ( a − b ) ( a + b ) , we have
( x − 1 6 ) ( x + 1 6 ) ( x − 1 4 ) ( x + 1 4 )
= ( x 2 − 1 6 2 ) ( x 2 − 1 4 2 )
= ( x 2 − 2 5 6 ) ( x 2 − 1 9 6 )
Now, since 2 5 6 = 2 2 6 + 3 0 and 1 9 6 = 2 2 6 − 3 0 , we have
( x 2 − 2 5 6 ) ( x 2 − 1 9 6 )
= [ x 2 − ( 2 2 6 + 3 0 ) ] [ x 2 − ( 2 2 6 − 3 0 ) ]
= [ ( x 2 − 2 2 6 ) − 3 0 ] [ ( x 2 − 2 2 6 ) + 3 0 ]
Now, using the algebraic identity a 2 − b 2 = ( a − b ) ( a + b ) once again, we have
= [ ( x 2 − 2 2 6 ) − 3 0 ] [ ( x 2 − 2 2 6 ) + 3 0 ]
= ( x 2 − 2 2 6 ) 2 − 3 0 2
= ( x 2 − 2 2 6 ) 2 − 9 0 0
The minimum value of this expression is simply − 9 0 0 , when ( x 2 − 2 2 6 ) 2 = 0 .
Hence, A = − ( − 9 0 0 ) = 9 0 0 , and we are done.
I'm a newbie here, so do advise me if I can improve on my solution in any way. And I'm not the Victor Loh who posted the question! I'm a different guy :)
Amazing solution! Good job!
Excellent solution
This solution uses a little bit of calculus.
(x-16) (x-14) (x+14) (x+16)
can be rearranged as
(x-16) (x+16) (x-14) (x+14).
Since
a^{2}-b^{2} = (a+b) (a-b),
then
(x-16) (x+16) (x-14) (x+14)
can be expressed as
(x^{2}-16^{2}) (x^{2}-14^{2})
which is equivalent to
(x^{2}-256) (x^{2}-196).
Expanding, we obtain
x^{4}-196x^{2}-256x^{2}+256 \times 196
which is equivalent to
x^{4}-452x^{2}+256 \times 196
Let y = x^{4}-452x^{2}+256 \times 196.
According to the Power Rule, if
y = x^{n},
then
dy/dx = nx^{(n-1)}.
Hence dy/dx
= 4x^{3}-(452 \times 2)x
= 4x^{3}-904x
In order for dy/dx to be minimum, dy/dx = 0.
Hence,
4x^{3}-904{x} = 0
Dividing both sides by x, we obtain
4x^{2}-904 = 0
4x^{2} = 904
x^{2}
= 904/4
= 226
Then -a
= (x^{2}-256) (x^{2}-196)
= (226-256) (226-196)
= (-30) (30)
= -900
Hence, a = 900.
Nice!
f ( x ) = ( x − 1 6 ) ( x − 1 4 ) ( x + 1 4 ) ( x + 1 6 ) = ( x 2 − 1 6 2 ) ( x 2 − 1 4 2 )
Let y = x 2 . Then:
f ( y ) = ( y − 1 6 2 ) ( y − 1 4 2 ) = y 2 − ( 1 6 2 + 1 4 2 ) y + 1 4 2 × 1 6 2 .
For minimum values of f(y), f ′ ( y ) = 0 . So:
2 y − ( 1 6 2 + 1 4 2 ) = 0
2 y = 1 6 2 + 1 4 2
y = 2 2 6
x 2 = 2 2 6
Let's plug this back into f(x):
f ( x ) = ( 2 2 6 − 1 6 2 ) ( 2 2 6 − 1 4 2 ) = − 3 0 × 3 0 = − 9 0 0
Thus, A = 9 0 0
-A=(x^2-256)(x^2-196) -> A=(256-x^2)(x^2-196) so dA/dx= - 2x(x^2 - 196)+ 2x(256 - x^2)= - 2x(2x^2 - 452)=0 so x^2 ={0 ، 226} -> so d^2A/dx^2 >0 when x^2=226 & <0 when x=0 so when x^2=226 the minimum value. so A=(226 - 256)(196 - 226)=900 #
On résout l'equation f ′ ( x ) = 0 si l'on voudrait trouver le minimum de f ( x ) . = = = d x d [ ( x − 1 6 ) ( x − 1 4 ) ( x + 1 4 ) ( x + 1 6 ) ] d x d [ ( x 2 − 1 9 6 ) ( x 2 − 2 5 6 ) ] d x d [ x 4 − 4 5 2 x 2 + 5 0 1 7 6 ] 4 x 3 − 9 0 4 x
f ′ ( x ) 4 x 3 − 9 0 4 x x 3 − 2 2 6 x x ( x − 2 2 6 ) ( x + 2 2 6 ) x = − 2 2 6 ou = = = = x = 0 0 0 0 0 ou x = 2 2 6
Donc, le minimum de f ( x ) est − 9 0 0 .
Problem Loading...
Note Loading...
Set Loading...
I decided to expand the polynomial because it seemed there were expressions in the form of: ( a + b ) ( a − b ) = a 2 − b 2
( x − 1 6 ) ( x + 1 6 ) ( x − 1 4 ) ( x + 1 4 ) = ( x 2 − 2 5 6 ) ( x 2 − 1 9 6 ) = x 4 − 4 5 2 x 2 + 5 0 1 7 6 . In order to find the critical points (local mins, local maxes), one should take the derivative of the function above and set it to 0. This leaves:
4 x 3 − 2 2 6 x = 0
4 x ( x 2 − 2 2 6 ) = 0
x = 0 or x 2 = 2 2 6
There is no need to plug in x = 0 because it gives the value 1 6 × 1 4 × 1 6 × 1 4 = s o m e t h i n g b i g and we know the answer must be negative.
Notice how I kept the second possible solution in the form of x 2 = 2 2 6 . This was because x 2 = 2 2 6 plugs in nicely to the original equation when it's in the form of: ( x 2 − 2 5 6 ) ( x 2 − 1 9 6 )
We find that: − A = ( 2 2 6 − 2 5 6 ) ( 2 2 6 − 1 9 6 ) = − 3 0 × 3 0 .
− A = − 9 0 0 So the final answer is:
A = 9 0 0 .